HUBUNGAN ANTARA KECERDASAN EMOSIONAL DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI SEKOLAH MENENGAH PERTAMA ALBANNA DENPASAR - Nurhayati; Muhtadi; Abdul Rouf (Arsy : Jurnal Studi Islam, 2020)
Moral improvement is the most important mission carried out by all the messengers of Allah, which, especially by the Prophet Muhammad and ESQ, is one of the answers to the moral degradation of the nation's generation and the moral decline. This study aims to determine the effect of Emotional Intelligence and Spiritual Intelligence (ESQ) on the morality of students in SD Muhammadiyah 1 Denpasar. The sample of this study involved 100 students inDenpasar Muhammadiyah 1 Elementary School who were determined as respondents.In this study there are three variables, namely emotional intelligence, spiritual intelligence, morality. Data collection methods using questionnaires distributed to students ingrades IV, V, VI in S D Muhammadiyah 1Denpasar as respondents then processed through Multiple linear regression analysis using SPSS version 1 6 software . Based on hypothesis testing it was found that (1). There was a significant effect of emotional intelligence on students' morality inMuhammadiyah 1 Elementary SchoolDenpasar p = 0,000 (2). There is a significant influence of spiritual intelligence on students' morality at Muhammadiyah 1 DenpasarElementary School 0,000 (3). There is a simultaneous significant effect of Emotional Intelligence and Spiritual Intelligence (ESQ) on the morality of students of SD Muhammadiyah 1 Denpasar p = 0,000 with a coefficient of determination of 6 9, 2%.Based on the results of this study, the authors advise all teachers and also school residents in SD Muhammadiyah 1 Denpasar in general to always strive to encourage the creativity of students so that aspects of emotional and spiritual intelligence can be improved so that the combination of right and left brain or EQ, SQ and IQ become more balanced.